2018
DOI: 10.1097/igc.0000000000001166
|View full text |Cite
|
Sign up to set email alerts
|

Potential Significance of Peptidome in Human Ovarian Cancer for Patients With Ascites

Abstract: We identified the peptidome patterns of patients with OC and benign gynecological conditions, and these differentially expressed that peptides might play an important role during occurrence and development of OC and will be in hope to explore bioactive peptides in the pathogenesis of OC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…With the development of mass spectrometry, several studies have focused on the identification of the peptide biomarkers in diseases (11)(12)(13). Up to now, the peptidome of the urine from healthy control and ovarian cancer patients and the peptidome of the ascites from benign gynecological conditions and ovarian cancer patients have been analyzed (36,37), the serum peptidomes of control and ovarian cancer patients have not been studied before. However, none of the differentially expressed peptides in this study were found in the preceding studies.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of mass spectrometry, several studies have focused on the identification of the peptide biomarkers in diseases (11)(12)(13). Up to now, the peptidome of the urine from healthy control and ovarian cancer patients and the peptidome of the ascites from benign gynecological conditions and ovarian cancer patients have been analyzed (36,37), the serum peptidomes of control and ovarian cancer patients have not been studied before. However, none of the differentially expressed peptides in this study were found in the preceding studies.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the combination of serum amyloid A1, albumin, serotransferrin, human epididymis protein 4 (HE4) and CA125 elevated the diagnostic capacity for differentiating benign and malignant OC (140). Increased expression of 52 peptides and decreased expression of 52 peptides were detected in the ascites fluid of OC patients compared to that of those with benign gynecological conditions (150). Label-free liquid chromatography-mass spectrometry was performed between favorable prognosis and poor prognosis primary HGSOC specimen and revealed that higher expression of 288 proteins was found in the favorable prognosis cluster, while higher expression of 370 proteins was found in the poor prognosis cluster (141).…”
Section: Proteomicsmentioning
confidence: 99%
“…It also provides a brand‐new idea to explore biomarkers for accurate or early diagnosis, prognosis and treatment management (Schrader et al, 2014). The samples used for analysis vary from those obtained by invasive acquisition, such as tissue (Li et al, 2020; Liu et al, 2018), blood (Tammen et al, 2007) and ascites (Huang et al, 2018), to those obtained by easy and noninvasive acquisition, including saliva (Amado et al, 2010), sweat (Yu et al, 2017), urine (Sirolli et al, 2019) and human breast milk (Campanhon et al, 2019). Current studies on peptidomics of human breast milk are focused on the protective factors for infants and mothers such as antimicrobial peptides (Dallas et al, 2013).…”
Section: Introductionmentioning
confidence: 99%